Organic Learning Gardens in Higher Education: Do They Improve Kindergarten Pre-service Teachers’ Connectedness to and Conception of Nature? - Pérez-López, Raquel; Eugenio-Gozalbo, Marcia; Zuazagoitia, Daniel; Ruiz-González, Aritz (Frontiers in Psychology, 2020)
Studies have shed light on the idea that people who have experiences in natural settings might be more aware of the environment. Learning gardens, as outdoor contexts, might contribute to the development of students’ affective relations towards nature, pro-environmental attitudes, and protective actions; neverthless these aspects begging to be explored. This preliminary research investigates the impact that the use of organic gardens to teach natural sciences at university has on kindergarten pre-service teachers’ connectedness to and conceptions of nature. The research follows a pre/post design and it uses a mixed methods approach. A total of 74 students completed four quantitative scales (INS, CCC, LCN, NR-6), and 66 of them an open question about the concept of nature. After the garden experience, students scored higher in all the scales, nevertheless the change was significant only for INS and CCC. The phenomenographic analysis evidenced an initial predominant static and non-social concept of nature, biased towards the most obvious biological elements. After the garden-based learning experience, more informed conceptions of nature -including notions of complexity and systemic character- increased from 7 to 19%; however, statistical comparison was not significant. In spite of the absence of concluding results, further research is required to assess the role that learning gardens may play regarding connectedness to nature and pro-environmental behaviors.